2017
DOI: 10.1177/2050640616673517
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with evidence‐based multidisciplinary guidelines on perihilar cholangiocarcinoma

Abstract: Background: Discrepancies are often noted between management of perihilar cholangiocarcinoma (PHC) in regional hospitals and the eventual treatment plan in specialized centers. Objective: The objective of this article is to evaluate whether regional centers adhere to guideline recommendations following implementation in 2013. Methods: Data were analyzed from all consecutive patients with suspected PHC referred to our academic center between June 2013 and December 2015. Frequency and quality of biliary drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…As endoscopic stenting in malignant hilar strictures (MHSs) is an advanced procedure with a relatively high risk of failure, and survival is severely hampered after failed drainage [156,157], the endos-copistʼs experience is even more important for MHSs than for distal malignant biliary strictures, as is the prompt availability of PTBD. Nevertheless, many patients with MHS are admitted to referral centers with a biliary stent already in place [158].…”
Section: Particular Casesmentioning
confidence: 99%
“…As endoscopic stenting in malignant hilar strictures (MHSs) is an advanced procedure with a relatively high risk of failure, and survival is severely hampered after failed drainage [156,157], the endos-copistʼs experience is even more important for MHSs than for distal malignant biliary strictures, as is the prompt availability of PTBD. Nevertheless, many patients with MHS are admitted to referral centers with a biliary stent already in place [158].…”
Section: Particular Casesmentioning
confidence: 99%
“…The more than twofold higher resection rate in patients diagnosed in academic centres compared to non‐academic centres suggests that some patients were eligible but not considered and not referred for surgery. A previous study in an tertiary referral center already observed that the assessment of resectability at the referring center was not always accurate 15 . The study found that one‐third of patients referred with initially presumed unresectable disease were considered resectable at the tertiary center.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study in an tertiary referral center already observed that the assessment of resectability at the referring center was not always accurate. 15 The study found that one‐third of patients referred with initially presumed unresectable disease were considered resectable at the tertiary center. However, since the study only included referred patients the problem was likely underestimated, which is demonstrated by the difference in resection rate in the present nationwide study.…”
Section: Discussionmentioning
confidence: 99%
“…The United European Gastroenterology Journal is keen on serving its readers with material that has the potential to improve their clinical practice 2 . There are a number of areas with considerably large clinical practice variation that could benefit from better standardization 3–5 . With continuously increasing information density, many appreciate seeing decisive papers such as clinical guidelines in the United European Gastroenterology Journal .…”
mentioning
confidence: 99%
“…2 There are a number of areas with considerably large clinical practice variation that could benefit from better standardization. 35 With continuously increasing information density, many appreciate seeing decisive papers such as clinical guidelines in the United European Gastroenterology Journal . Rightly so, guidelines and position papers continue to enjoy huge popularity with our readership.…”
mentioning
confidence: 99%